ON THE NUTRIENT CONTENT OF TREES OF DRY EVERGREEN FOREST IN NORTHEASTERN THAILAND - Prachaiyo, Buared; Tsutsumi, Toshio (วารสารวนศาสตร์ไทย, 2022)
The nutrient concentration was analyzed for above ground part of 40 trees in a dry evergreen forest in Khon Kaen University Farm at Chulabhorn Dam, about 140 km. West from Khon Kaen City. The nutrient concentration rather widely varied from tree to tree within same organ. The factors concerning those variations were examined. However, there was no clear relationship between nutrient concentration and tree size for each organ, and the difference between species was not significant. While, some nutrient elements such as nitrogen and phosphorus in leaves changed with specific leaf area. Nitrogen concentration in leaves was rather related with phosphorus and potassium, and calcium concentration was related with magnesium. Calcium and magnesium concentrations in this forest were higher than the other forest reported. The relationships between tree size and the accumulation of nutrient in the above ground part of tree were examined, and the equations were determined for each element.